Kedudukan Wanita dalam Masyarakat Desa Parannapa Jae Kecamatan Barumun Tengah Kabupaten Padang Lawas Ditinjau dari Pemikiran Fatima Mernissi - Harahap, Abdul Humala; Nasution, Hasnah; Ismahani, Siti (ANWARUL, 2023)
The majority of people understand that leadership can only be done by men. Memissi argues rights belong to men, it is an application of the granting of rights to women which is interpreted as amar ma'ruf nahi munkar, it has been recognized as having the same. This study aims to describe how the position of women in Parannapa Jae Village is from a religious, social and cultural perspective in terms of Fatima Mernissi's thoughts. This study used a qualitative/field research method. The data used in this study are library research with observation, recap of interview results, reading and researching relevant or relevant to this research. The findings from this study are that the position of women from a religious perspective in Parannapa Jae Village has fulfilled their rights as women, Islam elevates the status of women by providing education that requires humans to be fair in any way. Such as the social sector, there have been changes with the increasing quality of women's education so that they can elevate their status in the economic, political, and women's families. Women according to Fatima Memissi theologically have a high position is equal to men, women have the same equality as men according to their nature.